Alaṅkāraśāstrīyaṃ Sarasvatīkaṇṭhābharaṇam - Bhoja,Siddhartha, Sundari (Indira Gandhi National Centre for the Arts)
Treatise on the fundamentals of Sanskrit poetics; critical edition
Keywords: Sanskrit poetry / History and criticism; Poetics